Thinking Is Modulated by Recent Linguistic Experience: Second Language Priming Affects Perceived Event Similarity. Issue 3 (3rd May 2016) - Montero‐Melis, Guillermo; Jaeger, T. Florian; Bylund, Emanuel
Abstract: Can recent second language (L2) exposure affect what we judge to be similar events? Using a priming paradigm, we manipulated whether native Swedish adult learners of L2 Spanish were primed to use path or manner during L2 descriptions of scenes depicting caused motion events (encoding phase). Subsequently, participants engaged in a nonverbal task, arranging events on the screen according to similarity (test phase). Path versus manner priming affected how participants judged event similarity during the test phase. The effects we find support the hypotheses that (a) speakers create or select ad hoc conceptual categories that are based on linguistic knowledge to carry out nonverbal tasks, and that (b) short‐term, recent L2 experience can affect this ad hoc process. These findings further suggest that cognition can flexibly draw on linguistic categories that have been implicitly highlighted during recent exposure. Open Practices: This article has been awarded an Open Data badge. All data are publicly accessible via the Harvard Dataverse athttp://dx.doi.org/10.7910/DVN/QOD8ZU . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .